HUBUNGAN ANTARA MOTIVASI BERPRESTASI PEMBUATAN POLA KONSTRUKSI DENGAN PRESTASI BELAJAR MENJAHIT SISWA SMK ADHI YUDYA KARYA PATEAN KENDAL JAWA TENGAH - Siswati Siswati (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2015)
The objectives of this research are to know (1) motivation to achieve in creating design construction, (2) Sewing achievement, (3) the correlation between motivation to achieve creating design construction and sewing achievement. The type of the research is ex-post facto. Data are collected by questionnair and documentation. Data analysis techniques: descriptive analysis and hypothesis test uses product moment correlation begun by pre-requisite analysis, that is, normality and linearity examination. The results show that motivation to achieve in creating design construction is categorized high by relative frequency 48.38% and the sewing achievement is fair by relative frequency 61.29%. Based on correlation test, the result of rxy 0.550 >r tabel 0.254. It means that there is positive and significant correlation between motivation to achieve in creating design construction and sewing achievement.